Modelling COVID-19 contagion: risk assessment and targeted mitigation policies - Cont, R; Kotlicki, A; Xu, R (2020)
We use a spatial epidemic model with demographic and geographic heterogeneity to study the regional dynamics of COVID-19 across 133 regions in England.